Edukasi Kelompok Dalam Mengurangi Kecanduan Bermain Game Terhadap Siswa SD - Nudin Nudin; Wa Ode Reska Prasetya; Wa Ode Arwati Wangi (Lembaga Pengembangan Kinerja Dosen, 2024)
Online game addiction is a problem that has received attention from the wider community. Currently, much research is focused on efforts to reduce the level of online game addiction. This research aims to reduce the habit of playing online games through group discussion techniques among students at SDN 64 Buton District. Lasalimu, Kab. Buton, Southeast Sulawesi. This type of research is classroom action research. The research subjects were 10 students who were determined using purposive sampling techniques. Data collection instruments include a questionnaire on online game playing habits and observation guidelines. Testing the differences in students' online game playing habits from before being given guidance services using group discussion techniques to after being given guidance services using group discussion techniques was analyzed using the t-test formula. The results of data analysis show that the percentage of online game playing habits is 90.9%, while the average posttest percentage result is 57.6%. The research results showed that there was a decrease in the habit of playing online games through group discussion techniques among class VI students at SDN 64 Buton, Kec. Lasalimu, Kab. Buton, Southeast Sulawesi. This research is useful for teachers as consideration in reducing the habit of playing online games through group discussion techniques.